KERAGAAN HASIL GABAH DAN KARAKTER AGRONOMI SEPULUH VARIETAS PADI UNGGUL DI SLEMAN, YOGYAKARTA - Bambang Sutaryo; Joko Pramono (Agrin, 2016)
Yied and agronomic characters performance of ten superior rice varieties in Sleman, Yogyakarta. Study onyied and agronomic characters performance usin superior rice varieties was conducted at Blendangan,Tegaltirto,Berbah, Sleman, Yogyakarta from June to September of 2015. Six superior rice varieties namely Sidenuk, Inpari1, Inpari 10, Inpari 19, Inpari 23, and Inpari 30 were planted using seedling of 15 days with one seedling per hillin jajar legowo 4:1 system, with plant spacing of 25 x 12,5 x 50 cm. Plot size per variety was 1000 m2.Meanwhile,four populair varieties such as Sintanur, Pepe, Ciherang, and Situ Bagendit planted using the same populationby farmers were used as checks. Data were analyzed using t test. Inpari 19 and Inpari 30 gave the highest yield of7.5 and 7.3 t/ha, respectively, compared with check varieties and the other varieties tested. The highest yield onInpari 19 and Inpari 30 were contributed by the highest of the number of filled grains, total grain number, andthe panicle number. Inpari 19 showed earliest maturity (104 days), meanwhile, the other varieties were mediummaturity (107-124 days). Inpari 19 gave the highest profit compared with the others superior varieties tested andthe most preferred by farmers because of more taste, more white color, more shiny, and more fragrant.Key words: yield, agronomic characters, Inpari, “jajar legowo” ABSTRAKPenampilan hasil dan karakter agronomi sepuluh varietas unggul di Sleman, Yogyakarta. Pengkajianterhadap penampilan hasil dan karakter agronomi menggunakan varietas unggul padi dilaksanakan diBlendangan,Tegaltirto, Berbah, Sleman, Yogyakarta dari Juni hingga September 2015. Enam varietas yaituSidenuk, Inpari 1, Inpari 10, Inpari 19, Inpari 23, dan Inpari 30 ditanam dengan bibit berumur 15 hari dengan satubibit per lubang pada teknik jajar legowo 4:1, dengan jarak tanam 25 x 12,5 x 50 cm. Ukuran plot size per varietasadalah 1000 m2. Sedangkan empat varietas yang sudah dikenal petani yaitu Sintanur, Pepe, Ciherang, dan SituBagendit ditanam dengan cara yang sama oleh petani digunakan sebagai pembanding. Data dianalisismenggunakan uji t. Inpari 19 dan Inpari 30 masing-masing memberi hasil tertinggi sebesar 7,5 dan 7,3 t/ha,dibandinkan dengan varietas pembanding dan varietas lain yang dikaji. Hasil tertinggi pada Inpari 19 dan Inpari30 dikontribusi oleh jumlah gabah isi, jumlah total gabah dan jumlah malai yang tinggi. Inpari 19 menunjukkanumur paling cepat (genjah) yaitu 104 hari, sementara varietas lainnya berumur sedang (107-124 hari). Inpari 19memberi keuntungan tertinggi dibandingkan dengan varietas unggul lainnya, dan paling disukai petani karenalebih pulen, lebih putih, lebih berkilap, dan lebih wangi.Kata kunci: hasil, karakter agronomi, Inpari, “jajar legowo”